Effect of enzymes, hydrocolloids, and emulsifiers on qualities of dough and bread made from whole grain wheat flour - Tebben, Lauren Renae (Kansas State University, 2019)
Despite the associated health benefits of whole grains, consumption of whole grain products remains far below the recommended levels. Whole grain wheat flour has gained considerable attention as a breadmaking ingredient due to its nutritional and health benefits. Compared to white bread, whole wheat bread has a small loaf volume and hard crumb texture, creating unique challenges for the baking industry and for consumer acceptability. Dough conditioners and bread improvers within the classes of enzymes, emulsifiers, and hydrocolloids have been widely studied in white pan bread, but less information has been published on their use in whole wheat bread. The objective of this research was to determine effects of common enzymes, emulsifiers, and hydrocolloids on whole wheat bread properties, with a focus on dough physical and rheological properties, loaf volume, bread texture, and staling. Bread was prepared from whole wheat flour following AACC method 10-10.03. Enzymes (α-amylase, cellulase, glucose oxidase, maltogenic amylase, xylanase), emulsifiers (DATEM, polysorbate 80, soy lecithin, SSL, sucrose esters), and hydrocolloids (CMC, guar gum, HPMC, sodium alginate, xanthan gum) were added individually at three levels. Vital wheat gluten (VWG) was added as an additional, separate treatment at 2.5% (fwb) in the enzyme study. Dough rheological properties were determined by farinograph and mixograph. For the emulsifiers and hydrocolloids, additional dough properties were measured by the SMS/Chen-Hoseney stickiness test and the Kieffer rig uniaxial extensibility test. Specific volume was measured for fresh bread, and moisture content, texture profile analysis (TPA), and crumb structure were analyzed the following day. Moisture content and TPA were measured again after 3 and 7 days of storage at 22 °C to determine changes associated with staling. Effect on starch retrogradation was quantified by differential scanning calorimentry (DSC) after the 7 days. Hydrocolloids increased the water absorption and tended to decrease the stability of the dough, whereas enzymes had minimal effect on dough properties. Each enzyme and hydrocolloid increased specific loaf volume for at least one of the usage levels tested (P < 0.01). Of the emulsifiers, only polysorbate 80 and soy lecithin significantly increased loaf volume. Xanthan gum and HPMC resulted in the largest loaf volume among the hydrocolloids. Xylanase at the medium and high levels produced the greatest increase in loaf volume among the enzyme treatments, which also lead to the greatest reduction in fresh bread hardness. No enzyme was as effective as VWG at increasing loaf volume. VWG, maltogenic amylase, xylanase, HPMC, and xanthan gum reduced the rate of bread firming over 7 days. Sucrose esters and polysorbate 80 were the most effective anti-staling agents among the emulsifiers. DSC analysis revealed that maltogenic amylase nearly eliminated the endothermic peak for recrystallized amylopectin, showing this enzyme’s strong ability to reduce retrogradation in bread. This study demonstrated the specific application of enzymes, emulsifiers, and hydrocolloids in whole wheat bread to increase loaf volume and decrease initial crumb hardness and bread staling, which may help improve the sensory appeal of whole wheat bread and ultimately increase whole grain consumption.
Keywords: Whole wheat; Dough; Bread; Enzyme; Hydrocolloid; Emulsifier